한국음식에 대한 인식과 서비스품질의 차이 : 방한 외국인 관광객 비교문화연구 - 이수진; 이경희; Lee, Soo-Jin; Lee, Kyung-Hee (한국콘텐츠학회 논문지, 11(10), 2011)
This study examines international tourists 'perceived images and service quality of Korean foods. A survey was conducted to international tourists(Chinese, Japanese, American) visiting Korea. The results of study show that there is a significant difference in several attributes of Korean traditional foods as perceived by international tourists along their nationality. Particularly, American tourists tend to highly evaluate Korean foods as ones good for health. The perceived attractiveness of Korean foods in terms of color and shape is higher for Chinese and Americans than Japanese. A distinct difference is also found in the importance and performance attributes of perceived quality of Korean foods by the nationality of tourists. The results of IPA for the perceived quality of Korean traditional foods show that the restaurant facility and atmosphere are identified as the ones that need to be improved across all the tourists. 본 연구는 외국인 관광객들이 인식하는 한식에 대한 이미지와 서비스 품질의 차이를 조사하였다. 특히, IPA를 이용하여 외국인 관광객들이 인식하는 한식 서비스 품질 속성들에 관한 우선고려대상을 파악함은 물론, 이들이 국적별로 어떠한 차이가 있는지를 분석하였다. 본 연구를 위하여 중국, 일본, 미국 관광객들을 대상으로 한 설문조사가 진행되었고, 최종적으로 316개의 유효설문지가 분석에 이용되었다. 수집된 자료를 분석한 결과는 세 가지로 요약될 수 있다. 첫째, 한국 전통음식이 체질에 맞는 우수식품이라는 인식은 미국인이 동양문화권인 일본인과 중국인 보다 높은 것으로 확인되었고, 색과 모양의 아름다움에 대한 인식은 중국인과 미국인이 일본인 보다 높은 것으로 나타났다. 둘째, 한식 서비스품질 속성들에 대한 중요도와 실행도는 국적별로 뚜렷한 차이가 나타났다. 특히, 한식의 영양, 모양, 건강성, 음식관련이야기, 재료와 조리법에 관한 중요도 인식은 중국관광객들이 일본, 미국관광객들에 비해 더 높은 것으로 나타났다. 한식 서비스 품질 실행도에 관한 인식차이는 국적별로 좀 더 명확하게 나타났다 셋째, 국적별 관광객들이 인식하는 한국음식 서비스품질에 대한 IPA 결과, 공통적으로 음식점 시설/분위기의 개선이 우선적으로 필요한 사항이나, 국적별로 약간의 차이가 있는 것으로 나타났다.